2007
DOI: 10.1126/science.1135428
|View full text |Cite
|
Sign up to set email alerts
|

Thymine Dimerization in DNA Is an Ultrafast Photoreaction

Abstract: Femtosecond time-resolved infrared spectroscopy was used to study the formation of cyclobutane dimers in the all-thymine oligodeoxynucleotide (dT)18 by ultraviolet light at 272 nanometers. The appearance of marker bands in the time-resolved spectra indicates that the dimers are fully formed approximately 1 picosecond after ultraviolet excitation. The ultrafast appearance of this mutagenic photolesion points to an excited-state reaction that is approximately barrierless for bases that are properly oriented at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
616
5
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 507 publications
(670 citation statements)
references
References 39 publications
33
616
5
16
Order By: Relevance
“…In fact, the cyclobutane pyrimidine dimer is the most abundant lesion caused by ultraviolet radiation and consists of a reaction of the carbon-carbon double bonds of two proximal pyrimidine bases to form a cyclobutane ring. This reaction has been recently investigated by femtosecond time-resolved infrared spectroscopy [34] and it was revealed that in DNA samples irradiated at 266 nm, the intensity of infrared bands due to double-band stretch associated with the two carbonyl groups and the …”
Section: Damage In Thymine Groupsmentioning
confidence: 99%
“…In fact, the cyclobutane pyrimidine dimer is the most abundant lesion caused by ultraviolet radiation and consists of a reaction of the carbon-carbon double bonds of two proximal pyrimidine bases to form a cyclobutane ring. This reaction has been recently investigated by femtosecond time-resolved infrared spectroscopy [34] and it was revealed that in DNA samples irradiated at 266 nm, the intensity of infrared bands due to double-band stretch associated with the two carbonyl groups and the …”
Section: Damage In Thymine Groupsmentioning
confidence: 99%
“…Raman measurements on (dC) 10 were interpreted in terms of a complex equilibrium between duplex, tetraplex, and even octaplex structures [57]. The two-dimensional NMR spectra of Snoussi et al suggest that (rC) 5 adopts multiple intercalation topologies perhaps including an i-motif core terminated by double-stranded hemiprotonated duplexes or unpaired dangling strands [54].…”
Section: Structural Implicationsmentioning
confidence: 99%
“…In recent years, ultrafast laser spectroscopy has provided many new insights into excited states in nucleic acids [3][4][5][6][7][8][9][10]. Experiments on single bases are easier to interpret than those on multiple base systems ("base multimers"), and are more amenable to quantum chemical modeling [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…4 To fully understand the nature of the molecular specific interactions, it is essential to employ techniques that can interrogate the structural modifications underpinning these processes, and here we apply ultrafast time-resolved infrared spectroscopy (TRIR) for this purpose. ps-TRIR is now being demonstrated as a powerful technique for probing the photophysical properties of DNA, [5][6][7][8] and its strength stems from its ability to yield kinetic and structural information that goes beyond that obtainable from fluorescence or transient UV/visible absorption techniques.In this communication, we describe how ps-TRIR can be employed to investigate conformationally dependent photophysical properties of base-base interactions. Guanine is known to aggregate to form stacked species at high concentrations.…”
mentioning
confidence: 99%